2022
DOI: 10.17275/per.22.23.9.1
|View full text |Cite
|
Sign up to set email alerts
|

Preservice Teachers' Material Preparation Knowledge and Points to be considered While Developing the Material

Abstract: This study aimed to analyze knowledge of preservice teachers on material preparation process for mathematics lesson and their opinions about the points to be considered while developing material. In this context, in addition, it was intended to determine the preservice teachers' differences to use their knowledge on material preparation while developing materials in the course. To that end, 39 preservice teachers in total who studied in Elementary and Secondary School Mathematics Teaching Program at a state un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…When PSTs reflect on teaching practicum experiences to evaluate their attitudes, behavior, mentality, and competencies, it leads to new understandings and meanings for further development in PD [39] [43]. Furthermore, [34] and [30] reported that presenting content knowledge could not maximally provide PSTs as a problem-solving strategy. Still, they entail critical reflection practice to critically analyze, evaluate and fix problems for an ongoing process in stimulating their PC.…”
Section: Critical Reflection On Elt Practicum In Stimulating Psts' Pcmentioning
confidence: 99%
“…When PSTs reflect on teaching practicum experiences to evaluate their attitudes, behavior, mentality, and competencies, it leads to new understandings and meanings for further development in PD [39] [43]. Furthermore, [34] and [30] reported that presenting content knowledge could not maximally provide PSTs as a problem-solving strategy. Still, they entail critical reflection practice to critically analyze, evaluate and fix problems for an ongoing process in stimulating their PC.…”
Section: Critical Reflection On Elt Practicum In Stimulating Psts' Pcmentioning
confidence: 99%